Implementasi Pajak Digital di Kota Medan: Tantangan dan Solusi Ahmad - Aridho Aridho; Eko Sinaga; Fani Nadapdap; Widya Purba (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
Digital taxes have become a highlight in the era of economic digitalization, including in the city of Medan. The implementation of digital taxes in the city faces various challenges that need to be overcome to ensure success and fairness in tax collection. This article analyzes the main challenges faced in implementing digital taxes in Medan City, such as lack of awareness and understanding of digital taxes, difficulties in monitoring online transactions, and the incompatibility of regulations with technological developments. Apart from that, solutions needed to overcome these challenges were also discussed, such as increasing socialization and education about digital taxes, developing an efficient online transaction monitoring system, and revising tax regulations that are more adaptive to technological developments. It is hoped that this analysis can provide useful insights for the government and other stakeholders in implementing digital taxes effectively in Medan City.